PERANCANGAN KOLEKSI RESORT WEAR WANITA SEBAGAI RESPONS TERHADAP HOMOGENITAS DESAIN BUSANA DI BALI: WOMEN’S RESORT WEAR DESIGN IN RESPONSE TO FASHION DESIGN HOMOGENEITY IN BALI - Ayrine Fourensia Tejo; Rika Febriani; Evania Yessica (Universitas Trisakti, 2025)
Women’s Resort Wear Design in Response to Fashion Design Homogeneity in Bali Bali, as one of the most popular tropical tourist destination, has experienced rapid growth in its fashion industry, particularly in the resort wear category, which is favored by both domestic and international tourists. However, based on observations of various brands circulating in Bali, there is a tendency toward design homogeneity, characterized by repetitive silhouettes, colors, and fabric patterns, with minimal exploration. This stands in contrast to the preferences of modern consumers, especially Generation Z, who seek fashion with unique, expressive designs and a sense of exclusivity. In response to this problem, this study aims to design a women’s resort wear collection in the ready-to-wear deluxe category, oﬀering uniqueness through design exploration, complex construction techniques, and the use of premium materials. This research applies a qualitative approach through ﬁeld observations of 20 resort wear brands in Bali, supported by literature studies from various sources on fashion and market trends. The target market for this collection is Generation Z women aged 18–28 who visit Bali, who are conﬁdent, active on social media, and drawn to sexy, bold, and edgy styles. The resulting collection is expected to provide a solution to the design homogeneity in Bali’s fashion industry, while also enhancing the competitiveness of local fashion products in both national and international markets through a more innovative, explorative, exclusive, and tropically relevant design approach.